Meningocele with cervical dermoid sinus tract presenting with congenital mirror movement and recurrent meningitis - Erol, FS; Topsakal, C; Ozveren, MF; Akdemir, I; Cobanoglu, B (Yonsei Univ Coll Medicine, 2004)
Dermoid sinuses and meningoceles are seldom encountered in the cervical region. Besides, to the best of our knowledge, the coexistence of these types of congenital abnormalities with recurrent meningitis, as well as with mirror movement, has never been reported before. A 14-year-old female with the diagnosis of recurrent meningitis was referred to our clinic from the Department of Infectious Diseases. She had a cervical meningocele mass that was leaking cerebro-spinal fluid (CSF) and an associated mirror movement symptom. Spina bifida, dermoid sinus and meningocele lesions were demonstrated at the C2 level on computed tomography (CT) and magnetic resonance imaging (MRI). She underwent an operation to remove the sinus tract together with the sac, and at the same time the tethered cord between the sac base and the distal end of the spinal cord was detached. The diagnosis of dermoid sinus and meningocele was confirmed histopathologically. These kinds of congenital pathologies in the cervical region may also predispose the patient to other diseases or symptoms. Herein, a case of meningocele associated with cervical dermoid sinus tract which presented with recurrent meningitis and a rare manifestation of mirror movement is discussed. Neuro-surgeons should consider the possible coexistence of mirror movement and recurrent meningitis in the treatment of these types of congenital abnormalities.
Keywords: dermal sinus; meningocele; mirror movement; recurrent meningitis; spinal dysraphism